In vitro and in vivo studies of selenium nanoparticles coated bacterial polysaccharide as anti-lung cancer agents - Nourhan S. Shehata; Bassma H. Elwakil; Salma S. Elshewemi; Doaa A. Ghareeb; Zakia A. Olama (Microbial Cell Factories)
Abstract Microbial exopolysaccharides (EPSs) possess valuable biological functions and fascinating physicochemical properties. On the other hand, lung cancer is the primary contributor to global cancer-related deaths. However, health and safety concerns have prevented the identification and approval of any medications, including chemotherapeutic agents, for lung cancer treatment to date. The current study aims to enhance the production of bacterial EPS as a coating agent for the synthesis of selenium nanoparticles (AZEPS-SeNPs), to enhance their biological activity against pathogenic microbes, human lung adenocarcinoma cells (A549) in vitro, and diethyl nitrosamine (DEN)-induced lung cancer in vivo. The synthesized AZEPS-SeNPs exhibited a significant antifungal effect reaching 49.3 mm against Candida albicans. SeNPs and EPSs demonstrated a concentration-dependent synergistic antioxidant effect of 96.8%. Moreover, the synthesized nanoparticles showed a highly potent cytotoxic effect against A549 cells (1.724 ± 0.08 µg/mL) with a therapeutic index of 7.18 ± 0.21 that leads to increased reactive oxygen species (ROS) production. AZEPS-SeNPs demonstrated a proapoptotic effect on the lung adenocarcinoma A549 cell line by stimulating caspase 3 and Bax (7.08-fold and 6.505-fold, respectively), inhibiting the anti-apoptotic gene Bcl2, and arresting the cell cycle in the S phase. In vivo study revealed that the AZEPS-SeNPs-treated group showed improved histopathological examination of lung tissue sections. The present study concluded the efficiency of the synthesized bacterial EPS-SeNPs as multi-functional antimicrobial, anticancer and antioxidant agent.